The conjugates of ferrocene-1, 1′-diamine and amino acids. A novel synthetic approach and conformational analysis1. Issue 37 (7th October 2015) - Kovačević, Monika; Kodrin, Ivan; Cetina, Mario; Kmetič, Ivana; Murati, Teuta; Semenčić, Mojca Čakić; Roca, Sunčica; Barišić, Lidija
<x xml:space="preserve">Abstract</x> The first example of an orthogonally protected ferrocene-1, 1′-diamine based peptidomimetic with a stable intramolecular hydrogen bond pattern comprised of two β-turns is reported.